A randomized controlled trial to improve engagement of hospitalized patients with their patient portals. (19th October 2018) - Greysen, S Ryan; Harrison, James D; Rareshide, Charles; Magan, Yimdriuska; Seghal, Neil; Rosenthal, Jaime; Jacolbia, Ronald; Auerbach, Andrew D
Abstract: Objectives: To test a patient-centered, tablet-based bedside educational intervention in the hospital and to evaluate the efficacy of this intervention to increase patient engagement with their patient portals during hospitalization and after discharge. Materials and Methods: We conducted a randomized controlled trial of adult patients admitted to the hospitalist service in one large, academic medical center. All participants were supplied with a tablet computer for 1 day during their inpatient stay and assistance with portal registration and initial login as needed. Additionally, intervention group patients received a focused bedside education to demonstrate key functions of the portal and explain the importance of these functions to their upcoming transition to post-discharge care. Our primary outcomes were proportion of patients who logged into the portal and completed specific tasks after discharge. Secondary outcomes were observed ability to navigate the portal before discharge and self-reported patient satisfaction with bedside tablet use to access the portal. Results: We enrolled 97 participants (50 intervention; 47 control); overall 57% logged into their portals ≥1 time within 7 days of discharge (58% intervention vs. 55% control). Mean number of logins was higher for the intervention group (3.48 vs. 2.94 control), and mean number of specific portal tasks performed was higher in the intervention group; however, no individual comparison reached statistical significance. Observed ability to login and navigate the portal in the hospital was higher for the intervention group (64% vs. 60% control), but only 1 specific portal task was significant (view provider messaging tab: 92% vs. 77% control, P  = .04). Time needed to deliver the intervention was brief (<15 min for 80%), and satisfaction with the bedside tablet to access the portal was high in the intervention group (88% satisfied/very satisfied). Conclusion: Our intervention was highly feasible and acceptable to patients, and we found a highly consistent, but statistically non-significant, trend towards higher inpatient engagement and post-discharge use of key portal functions among patients in the intervention group.